Myeloid-Derived Suppressor Cells in Some Oncohematological Diseases - AV Ponomarev (Клиническая онкогематология)
Myeloid-derived suppressor cells are immature myeloid cells with immunosuppressive properties. The review presents characteristics of myeloid-derived suppressor cells. It includes phenotype variants, mechanisms of the suppressive effect on the immune system, and tumor recruitment mechanisms of myeloid suppressors. It provides a brief description of works which studied myeloid suppressor in oncohematological diseases including multiple myeloma, lymphomas, and leukemias.